The influence of trade war on the international economic system and its adjustment measures - Zhang, Haoning (International Journal of Global Economics and Management, 2024)
This paper discusses the influence of trade war on the international economic system and the corresponding adjustment measures. First of all, the trade war has had a negative impact on global economic growth, investment flows, international trade patterns and financial market fluctuations. Secondly, the trade war has caused international investment problems, which has led to the adjustment of the supply chain of multinational companies and the increase of investment uncertainty. Then, the financial market fluctuated and the currency, stock and bond markets were disturbed. Finally, by strengthening international cooperation, promoting trade multilateralism, lowering trade barriers and paying attention to sustainable development, we can meet the challenges brought by trade wars and look forward to establishing a more stable and sustainable international economic system in the future.